Surgical and audiological results of bone-anchored hearing aids: comparison of two surgical techniques - Amaral,Maria Stella Arantes do (2022)
Abstract Introduction: The bone-anchored hearing system has become the most viable treatment option for subjects with conductive or mixed hearing loss, who are unable to benefit from conventional hearing aids or middle ear surgery. Objective: To compare the surgical and audiological outcomes between the minimally-invasive Ponto surgery and a linear incision with soft tissue preservation techniques in bone-anchored hearing system recipients. Methods: A retrospective study was carried out from January 2017 to June 2018. Forty-two adult patients eligible for unilateral bone-anchored hearing system surgery with the Ponto system were included in the study. The implant and abutment lengths used varied from 3 to 4 mm and from 6 to 14 mm, according to the bone and skin thickness of the participants, respectively. Results: Twenty-two surgeries were performed using the minimally invasive Ponto surgery technique (52.4%) and 20 (47.6%) using the linear incision. The mean age of the subjects implanted with minimally invasive Ponto surgery and linear incision techniques were 42.0 and 33.3 years old, respectively. Ten male (45,5%) and 14 (70%) female patients were implanted using minimally invasive Ponto surgery and the linear incision techniques, respectively. There were no differences between pure tone audiometric thresholds and monosyllabic word recognition scores of the subjects, when comparing both surgical techniques. The minimally invasive Ponto surgery technique significantly reduced the surgical time compared to the linear incision technique. There were no differences between both surgical techniques for skin-related complications; (Holgers 3 and 4) which occurred in 18.8% for MIPS and in 25% for linear incision. Subjects included in the minimally invasive Ponto surgery technique group showed a superior cosmetic outcome, with no surgical scar or additional sutures. Conclusion: The surgical and audiological outcomes were satisfactory and were not correlated to the surgical technique selected in all subjects. When compared to the linear incision, the minimally invasive Ponto surgery technique showed reduced surgical time and superior esthetic outcomes in the postoperative follow-up.